The role of networks in the internationalization process of firms from emerging economies: The Nigerian perspective - Nkemdilim Iheanachor; Azuka Elvis Ozegbe (International Journal of Management, Economics and Social Sciences (IJMESS), 2021)
The purpose of this study was to explore the role of networks in the internationalization process of firms from emerging economies using Nigeria as a case study. A qualitative approach was employed to realize this purpose by using a sample of eight (8) top executives serving in four (4) leading Nigerian multinationals headquartered in Lagos. The participants had over 15 years of experience working with their respective firms in varying capacities. The study revealed that both social and business networks played critical roles in the internationalization of the investigated multinationals. However, it was observed that as much as social relationships remained crucial, they seemed less influential than the business networks in the subsequent international expansion activities of the firms. The findings contributed to the knowledge by providing insights into the international expansion patterns of Nigerian companies rarely found in empirical studies. By implication, multinationals are to embrace the relevant best practices for developing and managing firms' relationships with other stakeholders. Among the key messages are: prepare well, approach professionally, invest time, take a long-term view, learn from successful, failed and struggling relationships, and exit with least acrimony.
Keywords: F21; F44; M16; 330; Internationalization; networks; business relationships; Nigerian firms; partnerships